2012
DOI: 10.1142/s0217751x1250162x
|View full text |Cite
|
Sign up to set email alerts
|

CHARGED PION CONDENSATION PHENOMENON OF DENSE BARYONIC MATTER INDUCED BY FINITE VOLUME: THE NJL2 MODEL CONSIDERATION

Abstract: The properties of two-flavored massless Nambu-Jona-Lasinio model in (1+1)-dimensional R 1 × S 1 spacetime with compactified space coordinate are investigated in the presence of isospin and quark number chemical potentials µI , µ. The consideration is performed in the large Nc limit, where Nc is the number of colored quarks. It is shown that at L = ∞ (L is the length of the circumference S 1 ) the pion condensation (PC) phase with zero quark number density is realized at arbitrary nonzero µI and for rather smal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 73 publications
(69 reference statements)
1
54
0
Order By: Relevance
“…In the previous Section 2 (see 2.4) it was shown that charged PC does not take place in neutral quark matter with isospin asymmetry. But recently there have been found conditions that can be realized in real physical situations and can lead to the appearance of charged PC in dense quark matter [34,[37][38][39][40][41]. Some of these conditions are elaborated in the framework of the (3+1)-dimensional NJL model discussed in the previous section [40,41].…”
Section: Conditions Promoting the Appearance Of Charged Pion Conmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous Section 2 (see 2.4) it was shown that charged PC does not take place in neutral quark matter with isospin asymmetry. But recently there have been found conditions that can be realized in real physical situations and can lead to the appearance of charged PC in dense quark matter [34,[37][38][39][40][41]. Some of these conditions are elaborated in the framework of the (3+1)-dimensional NJL model discussed in the previous section [40,41].…”
Section: Conditions Promoting the Appearance Of Charged Pion Conmentioning
confidence: 99%
“…In this mini-review we discuss the present status of the charged PC phase in dense quark matter and, especially, pay attention to the factors promoting the emergence of charged PC phenomenon in dense quark matter. Namely, in the paper [34] it was found that this phase might be realized in dense baryonic system that has finite size. It was also demonstrated in [37] that in dense baryonic matter spatially inhomogeneous charged PC might appear, and more recently it was found in [38][39][40][41][42] that chiral imbalance is another interesting factor that can induce a charged PC phase.…”
Section: Introductionmentioning
confidence: 97%
“…THE PHASE STRUCTURE OF THE MODEL WITH ACCOUNT FOR THE CHEMICAL POTENTIAL AND TEMPERATURE If the term that is independent of σ is written out explicitly in (8), the effective potential can be rewrit ten as (9) Using the formula , ln which can be found, for example, in [19], after some simplifications, the effective potential can be rewritten as (11) where (12) (13) (14) here, Li are special functions polylogarithms [20], =…”
Section: The Effective Potential Of a Plane Three Dimensional Gross-nmentioning
confidence: 99%
“…Thus, a Lagrangian similar to the (1 + 1) dimensional Gross-Neveu model occurs in the study of one dimensional polymers, such as polyacet ylene [3,4], and a Lagrangian similar to the (2 + 1) dimensional Gross-Neveu model occurs in the study of two dimensional polymers (such as graphene, see, for example, [5]). Thus, the Gross-Neveu model that is used for the description of such systems with account for the influences of such parameters as tem perature, chemical potential, and external fields [5][6][7][8][9] is of special interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation